INTERCOMMUNICATION OF COMPOSITION OF AMNION LIQUID AND TO "MATURITY" OF SURFACTANT SYSTEM OF LUNGS FOR NEW-BORN CLINICALLY HEALTHY CALVES - Замазій, А. А. (Scientific Progress & Innovations, 2014)
Data are provided in article about aminokislotny structure and interrelation of amniotic liquid and "maturity" of surfaktantny system of lungs at newborn clinically healthy calfs. It is established that "maturity" of surfaktantny system of lungs was installed at 40,0% of calfs of firstcalf heifers. It was 1,80-1,70 times less (р<0,01) at calfs received from cows of the second - the third time. The total fraction phospholipid was 1,38 times higher than amniotic liquid, than at animals given rise in a condition of a hypoxia (р<0,01). The general content of amino acids in amniotic liquid of clinically healthy newborn calfs makes 330,39±7,52 nmol / 0,1 ml. The content of free amino acids was at the level 222,97±3,82 nmol / 0,1 of ml. From them, it was the share of part of irreplaceable amino acids 38,40±1,32 nmol / 0,1 to ml, and replaceable – 184,57±3,44 nmol / 0,1 to ml.